(untitled) (Comprehensive Journal of Science, 2026)
phytochemical screening of Mentha piperita leaves. and Nigella sativa Seeds Confirmed the presence of Several bioactive compounds in their methanolic extracts, including alkaloids, flavonoids, volatile oils, tannins, and Saponins, which are known for their therapeutic, and antimicrobial properties. The antibacterial activity of both extract was evaluated against two pathogenic bacterial strains using Standard laboratory methods. The methanolic extract of Nigella sativa exhibited strong inhibitorg activity. particularly against Gram-positive bacteria. whereas the alcoholic extract of Mentha piperita. Showed moderate antibacterial activity against both Gram-Positive and Gram – negative.bacteria. These findings suggest that both plants Contain bioactive compounds with potential use as natural antibacterial agents.